2018
DOI: 10.1089/ast.2017.1700
|View full text |Cite
|
Sign up to set email alerts
|

Earth Without Life: A Systems Model of a Global Abiotic Nitrogen Cycle

Abstract: Nitrogen is the major component of Earth's atmosphere and plays important roles in biochemistry. Biological systems have evolved a variety of mechanisms for fixing and recycling environmental nitrogen sources, which links them tightly with terrestrial nitrogen reservoirs. However, prior to the emergence of biology, all nitrogen cycling was abiological, and this cycling may have set the stage for the origin of life. It is of interest to understand how nitrogen cycling would proceed on terrestrial planets with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 87 publications
(104 reference statements)
1
58
0
Order By: Relevance
“…Comet delivery and impact fixation should also have supplied fixed nitrogen on prebiotic Earth; however, these mechanisms are thought to have supplied ϕNOX<2×109.3emcm2s1 and typically less, well within the range bracketed by lightning production (Laneuville et al, ). Airapetian et al () suggest that energetic protons from flares on the young Sun might also have powered nitrogen fixation and the supply of NOX to the surface; however, they do not quantify the magnitude of this supply.…”
Section: Kinetic Steady Statementioning
confidence: 99%
See 2 more Smart Citations
“…Comet delivery and impact fixation should also have supplied fixed nitrogen on prebiotic Earth; however, these mechanisms are thought to have supplied ϕNOX<2×109.3emcm2s1 and typically less, well within the range bracketed by lightning production (Laneuville et al, ). Airapetian et al () suggest that energetic protons from flares on the young Sun might also have powered nitrogen fixation and the supply of NOX to the surface; however, they do not quantify the magnitude of this supply.…”
Section: Kinetic Steady Statementioning
confidence: 99%
“…Under the assumption that the sole sink on NOX was destruction at high‐temperature hydrothermal vents, Wong et al () computed [ NOX] in the bulk ocean to be ≥10μM, and [ NOX] =20 mM for pCO 2 = 1 bar. Laneuville et al () conducted a systems model of the prebiotic nitrogen cycle, including cometary delivery, impact synthesis, and lightning as sources of fixed nitrogen and destruction at hydrothermal vents as the sole sink of oceanic NOX. They calculated [ NOX] ≈1μM to 10 mM in the bulk prebiotic oceans, depending on a number of variables including atmospheric nitrogen fixation rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A depiction of the Mesoproterozoic nitrogen cycle is shown in Figure . It is possible that abiotic processes generated additional marine NOx (Laneuville, Kameya, & Cleaves, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found a mantle nitrogen abundance of 7 ± 4 times the present atmospheric level (Johnson & Goldblatt, ) and coupled with modern subduction recycling rates (Mallik et al, ), these imply that the mantle is a long‐term sink of atmospheric nitrogen that has been monotonically sequestered over time. However, modern fluxes only apply if redox conditions were constant through time, yet models including nitrogen speciation change indicate that redox has a substantial effect on the atmospheric reservoir (Laneuville et al, ; Stüeken et al, ). The stable form of deep sea nitrogen for the Archean would have been NH 4 + (Holland, ), not oxidized species like NO 3 − as in modern oceans.…”
Section: Atmospheric Density In the Archeanmentioning
confidence: 99%